IMI-nonpathological human ocular tissue changes with axial myopia - Jonas, Jost B.; Spaide, Richard F.; Ostrin, Lisa A.; Logan, Nicola S.; Flitcroft, Ian; Panda-Jonas, Songhomitra (Investigative ophthalmology & visual science, 2023)
To describe nonpathological myopia-related characteristics of the human eye. Based on histomorphometric and clinical studies, qualitative and quantitative findings associated with myopic axial elongation are presented. In axial myopia, the eye changes from a spherical shape to a prolate ellipsoid, photoreceptor, and retinal pigment epithelium cell density and total retinal thickness decrease, most marked in the retroequatorial region, followed by the equator. The choroid and sclera are thin, most markedly at the posterior pole and least markedly at the ora serrata. The sclera undergoes alterations in fibroblast activity, changes in extracellular matrix content, and remodeling. Bruch's membrane (BM) thickness is unrelated to axial length, although the BM volume increases. In moderate myopia, the BM opening shifts, usually toward the fovea, leading to the BM overhanging into the nasal intrapapillary compartment. Subsequently, the BM is absent in the temporal region (such as parapapillary gamma zone), the optic disc takes on a vertically oval shape, the fovea-optic disc distance elongates without macular BM elongation, the angle kappa reduces, and the papillomacular retinal vessels and nerve fibers straighten and stretch. In high myopia, the BM opening and the optic disc enlarge, the lamina cribrosa, the peripapillary scleral flange (such as parapapillary delta zone) and the peripapillary choroidal border tissue lengthen and thin, and a circular gamma and delta zone develop. A thorough characterization of ocular changes in nonpathological myopia are of importance to better understand the mechanisms of myopic axial elongation, pathological structural changes, and psychophysical sequelae of myopia on visual function.